ANALISIS RASIO PROFITABILITAS DAN AKTIVITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA - Fadillah, Annisa; Wage, M Sunarto (SCIENTIA JOURNAL, 2021)
The stock price has an important value for a company, the high value of the share price in a company provides an opportunity for the company to generate dividends or capital gains. The development of stock prices certainly produces different analysis results that affect the company's net income so that the purpose of this study is to obtain tested explanative findings about the effect of profitability and activity ratios on share prices in mining companies on the Indonesia Stock Exchange. The research design used is quantitative which is processed using secondary data. The criteria established from 2015-2019. The measures used in this study are Return On Asset and Total Asset Turnover. The research method is processed using descriptive test, classical test which includes normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. Another method used is the hypothesis test which includes the t test and f test with the results of the study showing that: the partial profitability ratio Return on assets has no significant effect on stock prices, the activity ratio partially Total Asset Turnover has a significant effect on stock prices and simultaneously. Profitability and activity ratios have no significant effect on stock prices.